2011
DOI: 10.1371/journal.pone.0027721
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomine Fauna (Diptera: Psychodidae) and Putative Vectors of Leishmaniases in Impacted Area by Hydroelectric Plant, State of Tocantins, Brazil

Abstract: BackgroundAlthough leishmaniases are regarded as serious public health issues in the State of Tocantins, as consequence of the impact of environmental changes, small advances in taxonomic and ecological studies of Phlebotominae fauna are taking place in this state. The present study aimed to improve the knowledge about the sand flies, as well as about the aspects of the bioecology of leishmaniases vectors from Porto Nacional, a city that was directly impacted by the construction of Luís Eduardo Magalhães Hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 15 publications
1
37
1
4
Order By: Relevance
“…The Chao/ Jackknife indices calculated in the present study indicated that the sampling effort was suffi cient to completely estimate the species richness in the studied region. Several recent studies have described a high level of biodiversity of sand fl ies (>50 species registered in some of environments) in areas associated with hydroelectric systems in Brazil (21) (22) (23) . The present study is the fi rst to provide a longitudinal evaluation of sand fl y populations before and after the fi lling of a dam.…”
Section: Discussionmentioning
confidence: 99%
“…The Chao/ Jackknife indices calculated in the present study indicated that the sampling effort was suffi cient to completely estimate the species richness in the studied region. Several recent studies have described a high level of biodiversity of sand fl ies (>50 species registered in some of environments) in areas associated with hydroelectric systems in Brazil (21) (22) (23) . The present study is the fi rst to provide a longitudinal evaluation of sand fl y populations before and after the fi lling of a dam.…”
Section: Discussionmentioning
confidence: 99%
“…In Três Lagoas, 14 species were recorded between 2000 and 2006, totaling 4,277 specimens collected, with L. longipalpis corresponding to 87% (OLIVEIRA et al, 2010). Unlike these regions, faunal studies on these insects in Tocantins showed high species richness, with 48 species described in the municipality of Porto Nacional between 2004 and 2007, and revealing predominance of L. longipalpis, L. whitmani and L. sordellii (VILELA et al, 2011). In the Taquaruçu district, six months of research resulted in 767 sandfly specimens from 32 different species (MACHADO et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Its presence in Tocantins is unlikely, then. The presence of L. (L.) longipalpis was assumed only in municipalities where the information was missing, so given the wide distribution of L. longipalpis in Brazil [12] and, more specifically, in Tocantins State [29][30][31][32][33][34][35][36][37], the chances of its capture in a new sand fly survey are high.…”
Section: Discussionmentioning
confidence: 99%
“…From the scarce bibliographic records that were found (9), the vector was recorded in only 22 municipalities of Tocantins [29][30][31][32][33][34][35][36][37]. In contrast, there are records of human cases in 124 municipalities, which demonstrate the lack of entomological studies in the state ( Figure 5).…”
Section: American Visceral Leishmaniasis and Lutzomyia (Lutzomyia) Lomentioning
confidence: 99%
See 1 more Smart Citation